Critical reappraisal of short-acting bronchodilators for pediatric respiratory diseases - Amelia Licari; Sara Manti; Francesco Mastellone; Michele Miraglia Del Giudice; Gian Luigi Marseglia; Maria Angela Tosca; Asthma and Personalized Therapies Committee of the Italian Society of Pediatric Allergy & Immunology (SIAIP) (BMC, 2024)
Abstract Short-acting bronchodilators are a class of medications commonly used to treat asthma, chronic obstructive pulmonary disease, and other respiratory conditions. The use of these medications has evolved over time as we have gained a better understanding of their effectiveness and safety in the pediatric population. This comprehensive review synthesizes the current understanding of short-acting β2-agonists and short-acting anticholinergics in children. It addresses indications, contraindications, safety considerations, and highlights areas where further research is needed to guide the most effective use of short-acting bronchodilators.